Liberia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues and Statistical Appendix paper examines recent economic developments and medium-term outlook for Liberia. This paper focuses on economic developments during 2003 and 2004 and the medium-term challenges of reconstruction. The paper explores the pros and cons of adopting full (de jure) dollarization in Liberia. It reviews the theoretical arguments for and against adopting dollarization and the associated empirical evidence. The choices of monetary and exchange rate regimes made by other post-conflict countries are presented. The paper also assesses whether Liberia, in its current post-conflict situation, could benefit from dollarization.